2010
DOI: 10.1161/strokeaha.109.573576
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture in Poststroke Rehabilitation

Abstract: Background and Purpose-Acupuncture is a low-risk treatment with purported claims of effectiveness for poststroke rehabilitation. To comprehensively assess the efficacy of acupuncture in poststroke rehabilitation, we conducted a systematic review and meta-analysis of all randomized clinical trials of acupuncture for poststroke rehabilitation. Methods-We searched 7 English and 2 Chinese databases from inception to September 2009. Eligible studies included randomized clinical trials that evaluated the clinical ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
108
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(117 citation statements)
references
References 39 publications
3
108
0
Order By: Relevance
“…6 It also showed no difference in effectiveness between sham acupuncture and true acupuncture. 6 The lack of a positive effect of acupuncture in stroke rehabilitation reported by Kong and colleagues should be interpreted with caution because of the following limitations.First, the studies included in their systematic review were small (8-120 participants). Although one of the benefits of meta-analysis is that a synthesis of inadequately powered studies can yield interesting findings, a large number of studies would be required in order to show conclusive findings.…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…6 It also showed no difference in effectiveness between sham acupuncture and true acupuncture. 6 The lack of a positive effect of acupuncture in stroke rehabilitation reported by Kong and colleagues should be interpreted with caution because of the following limitations.First, the studies included in their systematic review were small (8-120 participants). Although one of the benefits of meta-analysis is that a synthesis of inadequately powered studies can yield interesting findings, a large number of studies would be required in order to show conclusive findings.…”
mentioning
confidence: 95%
“…A recent systematic review and meta-analysis showed that the use of sham acupuncture may contribute to study heterogeneity and affect the results (odds ratio 0.57, 95% confidence interval 0.30-0.41). 6 It also showed no difference in effectiveness between sham acupuncture and true acupuncture. 6 The lack of a positive effect of acupuncture in stroke rehabilitation reported by Kong and colleagues should be interpreted with caution because of the following limitations.…”
mentioning
confidence: 95%
See 3 more Smart Citations